Instructional Strategies for Engaging Online Learners: Do Learner-centeredness and Modality Matter? - Shi, Hui; Hur, Jaesung; Tang, Yuen Man; Vanessa (Online Learning, 2023)
This study explores how online instructors use different instructional strategies to engage learners, and the active learning indicators that they look for among their students. Additionally, it examines how modality—synchronous versus asynchronous—and instructor learner-centeredness relate to instructional strategy choices. Using a mixed methods approach with a concurrent triangulation design, 101 higher education online instructors were surveyed and 11 were interviewed. Findings show that the use of learner-centered strategies, particularly discussion, occurs at a high rate regardless of an instructor’s learner-centeredness or modality. Interestingly, instructors with high learner-centeredness reported greater use of lectures as a percentage of both synchronous and asynchronous courses than instructors with low learner-centeredness. This finding was counterbalanced by the high learner-centeredness group reporting significantly higher importance for having learners speak and post messages during class.